Impacto enlace ascendente YouTube 360° Live Video Streaming - Jiménez, Luis Roberto; Solera-Delgado, Marta; Toril-Genovés, Matías (My University, 2020)
At present, the most important service in mobile networks is video streaming, which is expected to generate 82% of all IP traffic volume by 2021. YouTube is one of the most popular video services on the Internet. In March 2015, YouTube added 360º video streaming service, which provides users with panoramic view and allows them to freely control their viewing direction during video playback. It is getting popular due to the recent availability of commercial devices that support 360 video interactivity as smartphones/tablets and head-mounted displays. 360° live video streaming is very challenging due to high bandwidth requirements. To address this problem, the video quality is adjusted according to the user viewport prediction. High-quality video is only streamed for the user viewport while the rest of the frame is transmitted in lower quality, reducing the overall bandwidth consumption, but this solution is not sufficient for the high requirements demanded by users. Thus, the optimization of this service is the utmost importance for network operators. In this paper, a study of the uplink in the broadcast video live section and its impact on the quality of experience perceived by the end-user is presented. The results show video quality, end-to-end latency and MOS (Mean Opinion Score). The analysis has been carried out by collecting traces at network level for TCP/IP metrics, HTTP messages by HAR traces every 300 s for video segment quality and end to end latency and user-level traces of each live 360 ° video session for S-KPIs (Service Key Performance Indicators).
Keywords: Vídeo; Redes sociales en Internet; LTE; Video streaming; QoE; Latency